ROTU's Perspective on Cyber-Security in Malaysia: Balancing Awareness and Security Threats - Shariffuddin, Mohd Dino Khairri; Ahmad Apandi, Laila Suriya; Ayub, Zainal Amin; Wallang, Muslimin; Saad, Ram Al Jaffri; Sagena, Uni W; Darus @ Md Junus, Mariah (2023)
Despite being a non-traditional social issue, cybersecurity is crucial in the context of technology development. The objective of this study is to investigate the level of awareness, perceived threat, and cybersecurity tools used by Reserve Officer Training Units (ROTUs) at public universities in Malaysia. A total of 2261 respondents, consisting of ROTU cadets participated through a Google Form Link. The study employed a quantitative method to conduct this population study. The primary objectives of this study were to assess the awareness level of cybersecurity among ROTU cadet respondents and to explore their perceptions regarding cybersecurity as a potential threat to the country. The findings of the study indicate that a significant majority of ROTU cadet respondents demonstrated a satisfactory level of awareness concerning cybersecurity. The results revealed that the majority of ROTU cadets associated cybersecurity predominantly with information technology. Additionally, they showed awareness of cybersecurity concepts such as hacking, protecting networks, safeguarding digital systems, and the role of cybersecurity in fostering innovation within the main database. Furthermore, the study found that a substantial majority of ROTU cadet respondents strongly agreed with the notion that cybersecurity represents a novel threat to the country. This indicates that these respondents perceive cybersecurity as a critical concern with the potential to pose significant risks to the nation's security and stability. Further research could explore specific areas where awareness might be lacking and design targeted interventions to enhance cybersecurity knowledge among ROTU cadets and other relevant groups